(untitled) (Orfeu, 2017)
Analytic study of John Coltrane’s interpretation of the song Na Baixa do Sapateiro (Bahia), composed by Ary Barroso. From phonographic record, we conducted a transcription in which we could observe an adaptation of the composition for use as improvisation practice linked to modal jazz, a territory explored by the saxophonist in his career. Firstly, we discuss the political issues that contributed to the diffusion of Brazilian music in the United States in the 1940s. Next, we address Coltrane’s relation to modal jazz, exposing its characteristics and emphasizing the importance of George Russel (2001) in the genesis of said style. Finally, we touch upon matters of performance in regard to the adaptations of the aforementioned composition, as well as aspects of the saxophonist’s improvisation. That said, this paper represents a contribution to improvisation studies, adding to the perspective of ethnomusicology and interpretive practices in popular music.